Customer's perspectives and risk issues on E-banking in Turkey; should we still be online? - (:unkn) unknown (My University, 2011)
The advent and expansion of globalization and the development of new technologies forced the banks to launch new channels to gain competitive advantage, reduce their costs, improve their financial services, enlarge their customer databases, progress their financial positions through innovative products and boost their general customer loyalty. Today, banks are switching to multi-channel distribution of financial services through internet. This paper tries to assess electronic banking in terms of a multi-channel distribution technique. The objective of this research is to examine the progression of Internet-banking in an emerging market, namely Turkey. This is done through a survey among online customers of Turkish banks and the proposition of strategies to control and fight against the risky issues associated with electronic banking (e-banking) activities. The usage percentage of online banking, the awareness of customers about the online services and their expectations from online banking activities in Turkey are evaluated through a survey and in depth interviews with online customers. This paper is organized as follows: the first part includes a brief literature review and examines previous research on the critical topics of "trends in global banking" and "risk issues in e-banking". Second part includes remarks on growth of online banking in Turkey. In the third part, the survey methodology is introduced and the results of the survey are analyzed. Fourth part concludes with some comments for further research. © Asli{dotless} Yüksel Mermod, 2010.
Keywords: Electronic banking; Internet banking; Online banking; Risk management in electronic banking; Turkey